Effect of Silica Aerogel Additive on Mechanical Properties of the Sugar Palm Fiber-Reinforced Polyester Composites. (24th December 2019) - Shahroze, R. M.; Ishak, M. R.; Sapuan, S. M.; Leman, Z.; Chandrasekar, M.; Asim, M.
Abstract : Silica aerogel (SA) was used as fillers in the sugar palm/polyester composite (SPF/PE). Their influence on tensile, flexural, and impact properties of the composite was determined by varying the additive concentration from 1-5 wt% in the resin. The findings from the study indicate that both the strength and modulus of SPF/PE improved significantly by adding SA. Maximum tensile, flexural, and impact strength occurred at an optimum filler concentration of 2-3 wt%. Similarly, the highest tensile and flexural modulus was achieved with 5 wt% and 2 wt%, respectively. The microstructure of SA-infused composites revealed less fiber pullout/slippage compared to the composites without filler.